NARRATIVIZING OPPRESSION AND SUFFERING: THEORIZING SLAVERY - Sanal Mohan (SOUTH ASIA RESEARCH 26(1): 5-40, 2006, 2006)
This article analyses the particular process by which memories of the slave experience of Pulayas, Parayas and similar castes are kept alive in contemporary Kerala by Followers of the Prathyaksha Raksha Daiva Sabha, a social and religious movement of Dalits started in 1909-10 by Poyikayil Yohannan in central Travancore. The article Shows how, over time, the Christian orientation of the movement was modified by its Dalit leaders, making intricate use of re-memorizing the slave experience. The outcome is that new myths and concepts were developed, evolving into new practices and discourses, including prominently the narrativization of oppression and suffering and rememory of slavery as part of initiation rituals into the movement.